Presentation and Outcome of a Cluster of Patients with Endogenous Endophthalmitis: A Case Series - Guber, J.; Saeed, M. U. (Klinische Monatsblätter für Augenheilkunde, 2015)
Background: The aim of this study was to investigate the clinical features and visual acuity outcomes associated with endogenous endophthalmitis. Material and Methods: Seven eyes of 6 patients treated at Epsom and St Helier University Hospitals between 2010 and 2013 were reviewed for endogenous endophthalmitis. Results: Patients were followed for a mean of 7 months (range 1 to 13). Positive blood cultures were obtained in 5 patients (83 %), including 1 patient with fungal isolates (17 %), two patients with Gram-positive isolates and another two with Gram-negative isolates. Five patients (83 %) were hospitalized at the time of diagnosis and 2 patients (33 %) died within 6 months of diagnosis. Initial treatment included vitreous tap and injection of intravitreal antibiotics. Only in one eye (14 %) were positive results from the biopsy obtained. Four eyes (57 %) achieved a final visual acuity of > 6/60. Patients with a Klebsiella endophthalmitis had worse visual outcome. Conclusions: Endogenous endophthalmitis is generally associated with high mortality and poor visual acuity outcomes. Gram-negative species are associated with poorer visual acuity. Vitreous biopsy has a weak diagnostic relevance as is it often negative.
Keywords: Endophthalmitis; endogene Endophthalmitis; Uveitis; Klebsiella